Math Problem Statement

Use mathematical induction to prove that 1 + 4 + 4^2 + ⋯ + 4^n = (4^(n+1) - 1) / 3 for all nonnegative integers n.

Solution

To prove the statement 1+4+42++4n=4n+1131 + 4 + 4^2 + \dots + 4^n = \frac{4^{n+1} - 1}{3} using mathematical induction, we follow these steps:

Step 1: Base Case (n = 0)

For n=0n = 0: The left side is simply 40=14^0 = 1. The right side is 40+113=413=33=1\frac{4^{0+1} - 1}{3} = \frac{4 - 1}{3} = \frac{3}{3} = 1.

Since both sides are equal, the base case holds.

Step 2: Inductive Hypothesis

Assume that the formula holds for some arbitrary nonnegative integer kk. That is, 1+4+42++4k=4k+113.1 + 4 + 4^2 + \dots + 4^k = \frac{4^{k+1} - 1}{3}.

Step 3: Inductive Step

We need to show that the formula also holds for k+1k + 1. That is, we want to prove: 1+4+42++4k+4k+1=4(k+1)+113.1 + 4 + 4^2 + \dots + 4^k + 4^{k+1} = \frac{4^{(k+1)+1} - 1}{3}.

Starting from the inductive hypothesis: 1+4+42++4k=4k+113.1 + 4 + 4^2 + \dots + 4^k = \frac{4^{k+1} - 1}{3}. Add 4k+14^{k+1} to both sides: 1+4+42++4k+4k+1=4k+113+4k+1.1 + 4 + 4^2 + \dots + 4^k + 4^{k+1} = \frac{4^{k+1} - 1}{3} + 4^{k+1}. To combine these terms, we rewrite 4k+14^{k+1} as 34k+13\frac{3 \cdot 4^{k+1}}{3}: =4k+11+34k+13.= \frac{4^{k+1} - 1 + 3 \cdot 4^{k+1}}{3}. Combine the terms in the numerator: =4k+1+34k+113=44k+113.= \frac{4^{k+1} + 3 \cdot 4^{k+1} - 1}{3} = \frac{4 \cdot 4^{k+1} - 1}{3}. Since 44k+1=4k+24 \cdot 4^{k+1} = 4^{k+2}, we get: =4k+213.= \frac{4^{k+2} - 1}{3}. This matches the right side of our formula for n=k+1n = k + 1.

Conclusion

Since the base case holds and we have shown that if the formula is true for n=kn = k, then it is also true for n=k+1n = k + 1, by the principle of mathematical induction, the formula is true for all nonnegative integers nn.

Would you like a more detailed breakdown of any steps or further clarification?


Here are some related questions to deepen understanding:

  1. What are the key principles behind mathematical induction, and how do they ensure validity?
  2. How does changing the initial base case affect the outcome of a proof by induction?
  3. Can you prove a similar formula for powers of another integer, such as 33 or 55?
  4. How would this proof look if you approached it using a different summation method?
  5. How does this type of series relate to geometric series in general?

Tip: In mathematical induction, always verify your base case and ensure your inductive step logically leads from the hypothesis to the conclusion.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Mathematical Induction
Geometric Series

Formulas

Sum of geometric series formula S = a(r^n - 1) / (r - 1)

Theorems

Principle of Mathematical Induction

Suitable Grade Level

Grades 11-12